Die Wunder des Pythagoras : Überlieferungen im Vergleich. - Scharinger, Stephan (Philippika / Altertumskundliche Abhandlungen., 2017)
Pythagoras of Samos (ca. 570−510 BC) was not only known in the ancient traditions as a natural philosopher, but also as a religious expert and miracle worker. In the present study, Stephan Scharinger dedicates himself to these miracle stories about Pythagoras. His considerations are based on the analysis and evaluation of the relevant source material, starting with the oldest written sources, which go back to the lifetime of Pythagoras, up to the Pythagorasvites of the Roman Empire. Based on this and with the help of the historical contextualization of Pythagoras (Pythagoreanism and Orphics, Pythagoras and the "Seven Wise Men", shamanism), Scharinger classifies the Pythagorean miracles depending on the Greco-Roman environment (ethnic religions, ancient Indian and Old Testament early church ideas). Miracle traditions in the Pythagorean traditions are finally examined in a two-fold comparison. The "internal" comparison shows parallels and differences between the miracle reports in Diogenes Laertios, Porphyrios of Tire and Iamblichus of Chalkis, while the "external" comparison shows the Pythagorean miracles with the reports around other miracle workers of the ancient Mediterranean world in a larger context. Reflections on the religious-historical context, on the discussion about Pythagoras as theios aner as well as on the classification of miracle works as "magical" or "religious" miracles complete the work off